Profesional Guru pada Pendidikan Anak Gangguan Intelektual - Fatmawati Fatmawati (Pedagogi: Jurnal Ilmu Pendidikan, 2013)
Education that should have a consistent pillar between educators and children who are educated themselves. However, Judging from the implementation of education that has been running, there is a visible gap. Namely the implementation of education for intellectually impaired children. Comparison between educators and students are very good still can improve the quality of education for them. This background by the competence of teachers as educators Tunagrahita. Children are intellectually impaired children who have mental retardation with developmental delays in almost all aspects of service and educational needs of its own. Education intellectually impaired children require different services with normal education. With this particular service, are expected to increase their knowledge and skills. An effort to develop their educational services are IEP (Individualized Educational Program). For this application takes the form of pedagogical competence, social personality, and professionalism that teachers should possess. Mastery of these competencies will extend to ornamental form of special educational needs the child's understanding, service, education and self-development. When all competencies possessed by educators, it will terealisasikanlah quality education. In other words, the professionalism of teachers in the education of children with intellectual disorder that will be.